Primula indica (Primulaceae), a new species from Dibang Valley of Arunachal Pradesh, India - Hajong, Bipankar; Bharali, Pankaj (Phytotaxa, 2025)
A new species Primula indica is found from Mayodiya paas area of Dibang Valley of Arunachal Pradesh is described and illustrated. It resembles to Primula vilmoriniana Petitm. which is belonging to the section Obconicolisteri but, differs in having small petiole, few flowered, calyx large, homostylous (vs. heterostylous), pedicel small, corolla lobe broadly obovate and quite large, corolla tube large, style large 8 mm (vs. small ca. 4 mm). The new species is preliminarily assigned as Data Deficient (DD) following the IUCN (2022) guidelines.